2006
DOI: 10.1176/appi.ajp.163.10.1784
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Ventral Striatal Response to Positive Stimuli in Depressed Versus Normal Subjects

Abstract: This finding 1) supports a pathophysiological model of depression that includes reward/motivational pathway dysfunction, 2) suggests a contributing neural substrate of the inability to experience pleasure or engage in rewarding activities, 3) provides greater specification of abnormalities of basal ganglia function in depression, and 4) may help guide treatment approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
144
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 362 publications
(163 citation statements)
references
References 0 publications
18
144
1
Order By: Relevance
“…However, their role has not been fully understood. To date, a couple of studies have demonstrated associations between depression and reduced neural responses during the viewing of pleasant facial expressions and words (Epstein et al, 2006;Monk et al, 2008;Surguladze et al, 2005) and during the sight and taste of pleasant chocolate stimuli (McCabe et al, 2009;McCabe et al, 2012). These findings point to the general nature of reduced reward responsiveness in depression, beyond monetary rewards.…”
Section: Social Rewards In Depressionmentioning
confidence: 97%
“…However, their role has not been fully understood. To date, a couple of studies have demonstrated associations between depression and reduced neural responses during the viewing of pleasant facial expressions and words (Epstein et al, 2006;Monk et al, 2008;Surguladze et al, 2005) and during the sight and taste of pleasant chocolate stimuli (McCabe et al, 2009;McCabe et al, 2012). These findings point to the general nature of reduced reward responsiveness in depression, beyond monetary rewards.…”
Section: Social Rewards In Depressionmentioning
confidence: 97%
“…Functional neuroimaging studies in MDD have consistently indicated hypoactivation in reward-processing regions, including the dorsal and ventral striatum [210-214] and a host of other reward structures, including the medial prefrontal cortex [215,216], the pregenual and subgenual anterior cingulate, and the medial frontal gyrus [217,218]. …”
Section: Reviewmentioning
confidence: 99%
“…Reduced mesolimbic activity in MDD has been found during reward anticipation and outcomes in both adults and children [210,219-227] and during reward learning [206]. For example, Smoski et al .…”
Section: Reviewmentioning
confidence: 99%
“…It has been proposed that the putative neural substrate of anhedonia may involve the dysfunction of a dopaminergic reward circuit. 17,18 However, only a limited number of neuroimaging studies have specifically attempted to confirm this hypothesis. To date, functional neuroimaging studies of anhedonia have focused exclusively on clinical populations, either SZ 19 or MDD.…”
Section: Introductionmentioning
confidence: 99%
“…To date, functional neuroimaging studies of anhedonia have focused exclusively on clinical populations, either SZ 19 or MDD. 17,18,20,21 For example, Keedwell et al (2005) linked the ventromedial prefrontal cortex (VMPFC) and the ventral striatal activity to anhedonia severity in MDD. Although these results have provided significant advancements in the neural characterization of anhedonia, it remains difficult to delineate clearly cerebral dysfunctions associated specifically with anhedonia from other dimensions of the illness.…”
Section: Introductionmentioning
confidence: 99%